2019
DOI: 10.1111/sjop.12564
|View full text |Cite
|
Sign up to set email alerts
|

Bullying bystander behaviors: The role of coping effectiveness and the moderating effect of gender

Abstract: Researchers have suggested that bystander behaviors and victim coping play an important role in counteracting the negative effects of bullying. The current study investigated the relationship between students’ ratings of coping effectiveness when addressing bullying and their behaviors as bystanders when witnessing bullying. Surveys were administered in a Midwestern, suburban school district. Some associations between perceptions of coping effectiveness and bystander behavior supported our hypotheses (e.g., co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…The nature of the association between bullying and social status appears to be more complex. Bullies tend to gained a certain popularity among the classroom group, and for this reason that may be supported in his/her actions by a subgroup of peers within the class (e.g., Parris et al, 2020). However, within the concept of social status among peers, the popularity and social preference by peers do not coincide, and the two constructs do not always correlate positively (van den Berg, Lansu, & Cillessen, 2020).…”
Section: Peer Social Status and Bullying Involvementmentioning
confidence: 99%
“…The nature of the association between bullying and social status appears to be more complex. Bullies tend to gained a certain popularity among the classroom group, and for this reason that may be supported in his/her actions by a subgroup of peers within the class (e.g., Parris et al, 2020). However, within the concept of social status among peers, the popularity and social preference by peers do not coincide, and the two constructs do not always correlate positively (van den Berg, Lansu, & Cillessen, 2020).…”
Section: Peer Social Status and Bullying Involvementmentioning
confidence: 99%
“…In general, non-productive coping, such as helplessness and retaliation, was less frequently recommended by students for victims compared with reference to others or productive coping [ 55 ]. Prior research has revealed a positive relationship between retaliation and being victims of cyberhate [ 20 ] as well as traditional or cyberbullying [ 30 , 31 , 46 , 56 ]. Regarding perpetrators, there is some evidence that several non-productive strategies, such as helplessness, self-blame, and retaliation, were positively correlated with offline and online aggression [ 31 , 35 , 47 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the gender of the bystanders might explain why some bystanders defended the victims whereas others did not (Espelage, 743 Bystander's Defending Behaviors Mebane, & Adams, 2004;Parris et al, 2020). Researchers have reported that girls, compared to boys, expressed higher levels of personal distress in response to empathic stimuli (Rose & Rudolph, 2006).…”
Section: Introductionmentioning
confidence: 99%